2019
DOI: 10.1007/s40472-019-00260-3
|View full text |Cite
|
Sign up to set email alerts
|

Belatacept and CD28 Costimulation Blockade: Preventing and Reducing Alloantibodies over the Long Term

Abstract: Purpose of Review Highlight developments in T and B cell biology that are helping elucidate the mechanisms underlying CD28 pathway blockade-mediated inhibition of alloantibodies in transplantation, and discuss recent clinical observations on the impact of belatacept on de novo and established HLA antibodies. Recent FindingsThe identification of T follicular helper cells as the CD4+ T cell subset required for optimal humoral immunity, along with newly identified roles for CD28 and the B7 molecules on B cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…This is in response to early work on allograft rejection, which demonstrated that T cells are both necessary and sufficient for allograft rejection (4,5). More recent work has focused on developing novel tolerogenic protocols that target the adaptive immune response using methods that include depletion of effector T cells (6), induction of CD4 + CD25 + Foxp3 + regulatory T cells (7) and blockade of co-stimulatory signals (8). The latter was achieved using monoclonal antibodies (mAb) or immunoglobulins (Ig) against cell surface molecules (CD4 (9); CD4 + DST (10); CD3 (11); non-depleting CD3 (12); CD40L (13); CD40L + CD28 (14); LFA-1 + + ICAM-1 (15); CD2 (16); CD2 + CD3 (17); LFA3-Ig (18); CD80 and CD86 (19); CD40 (20); and CTLA4-Ig (21) ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…This is in response to early work on allograft rejection, which demonstrated that T cells are both necessary and sufficient for allograft rejection (4,5). More recent work has focused on developing novel tolerogenic protocols that target the adaptive immune response using methods that include depletion of effector T cells (6), induction of CD4 + CD25 + Foxp3 + regulatory T cells (7) and blockade of co-stimulatory signals (8). The latter was achieved using monoclonal antibodies (mAb) or immunoglobulins (Ig) against cell surface molecules (CD4 (9); CD4 + DST (10); CD3 (11); non-depleting CD3 (12); CD40L (13); CD40L + CD28 (14); LFA-1 + + ICAM-1 (15); CD2 (16); CD2 + CD3 (17); LFA3-Ig (18); CD80 and CD86 (19); CD40 (20); and CTLA4-Ig (21) ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…23 Belatacept has reduced the incidence of de novo DSA, 8 but its mechanism of action is suboptimal for the purpose of inhibiting alloimmunity in that CTLA-4-Ig not only blocks CD28 costimulation but also prevents critical coinhibitory and regulatory activity mediated via CTLA-4. 10 As evidence supporting antagonism of the CD28 pathway to combat alloantibodies mounts, 19 it is foreseeable that more potent forms of CD28 blockade will be desired in cases of highly sensitized patients or potential costimulation blockade-based desensitization protocols. 6 Here, we demonstrate that selective CD28 blockade is better than CTLA-4-Ig at inhibiting the humoral alloresponse in a clinically relevant full allogeneic mismatch model and that this superior inhibition is mechanistically CTLA-4-dependent and Tfh cell specific.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility of mature effector Tfh cells engaged in cognate B cell interactions and not just naïve Tfh precursor CD4 + T cells to CD28 blockade has therapeutic implications. There has been resurgent interest in the use of CD28 costimulation blockade to attenuate alloantibody responses 6,19 . Several recent studies have reported a modest ability of belatacept to control nascent or preexisting HLA antibodies, 49‐51 and a belatacept‐based desensitization regimen helped mediate reductions in DSA in nonhuman primates 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the small cohort described in lung candidate above is the only known use of CD28 co-stimulation blockade in multimodal lung transplant desensitization protocols and larger scale trials are needed ( 42 ). The higher immunosuppressive effects are attractive in highly allosensitized patients, however safety and efficacy data are yet to be seen ( 48 ).…”
Section: Management Strategies: Waitlist and Allocation Considerations And Therapymentioning
confidence: 99%